A Comprehensive Assessment Tool for Patient Registry Software Systems: The CIPROS Checklist - Lindoerfer, D.; Mansmann, U. (Methods of Information in Medicine, 2015)
Background: Patient registries are an important instrument in medical research. Often their structure is complex and their implementation uses composite software systems to meet the wide spectrum of challenges.Objectives: For the implementation of a registry, there is a wide range of commercial, open source, and self-developed systems available and a minimal standard for the critical appraisal of their architecture is needed.Methods: We performed a systematic review of the literature to define a catalogue of relevant criteria to construct a minimal appraisal standard.Results: The CIPROS list is developed based on 64 papers which were found by our systematic review. The list covers twelve sections and contains 72 items.Conclusions: The CIPROS list supports developers to assess requirements on existing systems and strengthens the reporting of patient registry software system descriptions. It can be a first step to create standards for patient registry software system assessments.
Keywords: Checklist; patient registry software system; technical requirements